2006 Formal Methods in Computer Aided Design 2006
DOI: 10.1109/fmcad.2006.28
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Verification Complexity of a Multicore Coherence Protocol Using Assume/Guarantee

Abstract: Abstract-We illustrate how to employ metacircular assume/guarantee reasoning to reduce the verification complexity of finite instances of protocols for safety, using nothing more than an explicit state model checker. The formal underpinnings of our method are based on establishing a simulation relation between the given protocol M , and several overapproximations thereof, M1, . . . ,M k . EachMi simulates M , and represents one "view" of it. TheMis depend on each other both to define the abstractions as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…We applied the standard method for debugging cache coherence protocols: we built a formal model of our protocols and performed an exhaustive reachability analysis of the model for a small configuration size [28,25,8] using explicit-state model checking with the Murphi [11] model checker. We extended the DASH protocol model provided as part of the Murphi release, ran the resulting model through Murphi, and found that none of the invariants provided in the DASH model were violated by our changes.…”
Section: Verificationmentioning
confidence: 99%
“…We applied the standard method for debugging cache coherence protocols: we built a formal model of our protocols and performed an exhaustive reachability analysis of the model for a small configuration size [28,25,8] using explicit-state model checking with the Murphi [11] model checker. We extended the DASH protocol model provided as part of the Murphi release, ran the resulting model through Murphi, and found that none of the invariants provided in the DASH model were violated by our changes.…”
Section: Verificationmentioning
confidence: 99%
“…This is because exclusive [4] or non-inclusive [5] caching both incur three-way communication (i.e. among data requester, directory, and owner) to locate shared data and they also introduce nontrivial design and verification complexity [6].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, Abs #j employs assumptions that are justified by verifying some number of Abs #i's (further details of such meta-circular dependencies are discussed in Section II-A). In [1], we show that (i) each Abs #i has far less states than the original hierarchical protocol, (ii) the additive complexity of verifying the Abs #i's in turn is also far less than the complexity of the original protocol. However, as will be seen from Figure 3, even one Abs #i involves the product state space of one entire unit (such as 'Home cluster' in Figure 3) and two simplified units (such as 'Remote clusters' in Figure 3).…”
Section: Introductionmentioning
confidence: 94%
“…This is bad news, considering that the intra cluster protocol state space itself will be very large, and that any product of the states of three intra cluster protocols and one inter cluster protocol ( Figure 1) would be unacceptably large. In our previous work [1], we presented a compositional approach for partly mitigating this problem. The workflow of the approach is shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%